Avaliação dos riscos no elo fornecedor e produtor de uma Cadeia de suprimentos da indústria do gás natural - Oliveira, Ana Camila Rodrigues de (2017)
The Supply chain risk management (SCRM) consists in identifying risk sources and seeking means for preventing or reducing the negative impact of a particular event. The SCRM is an important part of supply chain management, as risks can cause sudden changes within the materials flow thorough the chain, causing loss for organizations. Still, although professionals and scholars acknowledge the importance of risk management, countless difficulties remain when executing the evaluation of risks in modern supply chains. In this context, this study aims at evaluating the risks among the producer-supplier bond from a piped gas supply chain. To achieve this goal, this study follows a quali-quantitative approach, which initially defines a conceptual theoretical structure through a systematic literature review. Afterwards, elects a pivot company and establishes the other chain members that will be studied. From that, the risks were identified in the companies and, then, the risks were evaluated in terms of probability of occurrence and gravity. It has been used the analytic hierarchy process (AHP) for hierarchizing the risks according to their importance, conforming specialists’ opinions. For the critical risks, it was used the Monte Carlo Simulation to simulate its probability of occurrence in different scenarios. To run this simulation, it was employed the Bayes Theorem with the purpose of understanding the probability of occurrence of a specific type of risk in the pivot company considering the existence of another type of risk in it’s most relevant client. According to other results obtained, it was verified that a specific risk confronted by an organization could replicate thorough the supply chain and generate damage in both financial costs and reputation for the companies involved. Furthermore, evidences show that it is important to invest in mitigation strategies for those risks that are crucial in order to reduce its likelihood and/or its impact for companies.